Impactful Activities of User Committee (A Case Study of Dharachaur Drinking Water and Sanitation User Committee) - Khatri, Bal Krishna (Cognition, 2025)
The main objective of this research paper is to explore the impactful activities of the Dharachaur Drinking Water and Sanitation User Committee (DDWASUC). The committee provides clean drinking water twice daily, totaling five hours of service, through 700 taps, two boreholes, two reservoir tanks, and one treatment plant. This innovative infrastructure has eliminated the need for expensive water pumps and other water sources in the designated community, making access to water more efficient and cost-effective for residents. Employing qualitative design, this research integrates key informant interviews, direct observations, and document analysis to comprehensively understand DDWASUC's impactful activities from May to September 2024. Applying Structural Functionalism theory, the research highlights the committee’s dual role in providing essential services and fostering social cohesion and collective identity. Beyond infrastructure, DDWASUC enhances community development through diverse initiatives. Recreational Picnic programs have evolved into platforms for social interaction, collaboration, and community bonding. Moreover, DDWASUC has implemented a financial assistance program for bereaved families, which promotes empathy and compassion while reinforcing community ties during challenging times. Additionally, the committee encourages health insurance enrollment among its members to facilitate access to healthcare. It has also introduced a student reward program and a souvenir publishing initiative to support academic achievement. These diverse initiatives underscore DDWASUC's commitment to addressing both the practical and emotional needs of the community, positioning it as a model for sustainable, community-driven change that empowers residents and fosters resilience in the face of challenges.